Analysis of Indonesia's Attractiveness as a Foreign Investment Destination - Lala Lolita; Gusganda Suria Manda; Hilmi Muhammad An Naafi Indrayanto; Vilensia Anggraeni; Vitho Bagus Permana (BIMA Journal (Business, Management, & Accounting Journal), 2026)
Purpose: This study aims to identify and analyze the main factors influencing Foreign Direct Investment (FDI) flows to Indonesia. This study is important because FDI plays a role in strengthening economic growth, encouraging technology transfer, and enhancing national competitiveness amidst global economic dynamics. Methodology: The study uses a Systematic Literature Review (SLR) approach by reviewing five selected scientific journals published between 2021–2025. The analysis process includes screening, quality evaluation, and comparison of methods, variables, and key findings from each study . Results: The synthesis results show that GDP, exports, exchange rate stability, political conditions, and governance have a significant influence on FDI. In addition, global geopolitical tensions also influence investment risk and capital movements. Findings: The study finds that institutional readiness and responsiveness to global uncertainty are now key factors for investors, complementing traditional economic indicators. Novelty: This study offers a new integration of economic, geopolitical, and institutional factors within a comprehensive analytical framework. Originality: The study provides a unique perspective on the interaction between global and domestic conditions in shaping the attractiveness of FDI in Indonesia. Conclusion: Indonesia can increase its FDI attractiveness through strengthening governance, economic stability, and adaptive strategies to global dynamics. Future research is recommended to focus on differences in FDI across sectors. Type of Paper: Systematic Literature Review.